Isolation of charantin from the fruit of Philippine-grown Momordica charantia L. (Fam. Cucurbitaceae) - Lejano, Raquel Celera 1944-
The alcoholic extract of the fruit of Philippine-grown Momordica charantia L. (Fam. Cucurbitaceae) yielded 0.024% on the dry basis of a mixture of sterol glucosides identified as charantin, m.p. 266-268(degrees C), decomp.; tetra-acetate, m.p. 167-170(degree C) by comparison with authentic samples. Silver nitrate-impregnated chromatography revealed charantin to be a mixture of two glucosides which strongly corresponds to β-sitosterol-β-D-glucoside and its dehydrosterol, 5,25-stigmastadien-3β-D-glucoside. The composition elucidation of the mixture was further confirmed by IR and NMR analyses.